1‐(Hydroxymethyl)‐1H‐benzotriazole: An Efficient Ligand for Copper‐Catalyzed Ullmann‐Type Coupling Reaction Leading to Expeditious Synthesis of Diverse Benzoxazoles and Benzothiazoles. Issue 33 (30th August 2019) - Singh, Mala; Bose, Priyanka; Singh, Anoop S.; Tiwari, Vinod K.
Abstract: Cu‐catalyzed Ullmann coupling was performed for the facile synthesis of diverse benzoxazoles and benzothiazoles in the presence of 1‐(hydroxymethyl)‐1 H ‐benzotriazole as ligand and K2 CO3 as base in anhydrous DMF at 120 0 C. Abstract : Cu–Catalyzed Ullmann coupling was performed for the facile synthesis of diverse benzoxazoles and benzothiazoles in the presence of 1‐(hydroxymethyl)‐1 H ‐benzotriazole/K2 CO3 in anhydrous DMF at 120 0 C.